Large‐scale InSAR monitoring of permafrost freeze‐thaw cycles on the Tibetan Plateau. Issue 2 (21st January 2017) - Daout, Simon; Doin, Marie‐Pierre; Peltzer, Gilles; Socquet, Anne; Lasserre, Cécile
Abstract: Multitemporal interferometric synthetic aperture radar (InSAR) observations are used to characterize spatial variations of the permafrost active layer and its temporal evolution in Northwestern Tibet. We develop a method to enhance InSAR performances for such difficult terrain conditions and construct an 8 year timeline of the surface deformation over a 60, 000 km 2 area. The ground movement induced by the active layer's response to climate forcing is limited to Cenozoic sedimentary basins and is spatially variable in both its seasonal amplitude (2.5–12 mm) and multiannual trend (−2 to 3 mm/yr). A degree‐day integrated model adjusted to the data indicates that subsidence occurs when the surface temperature exceeds zero (May to October) over areas where seasonal movements are large (>8 mm). The period of subsidence is delayed by 1–2 months over areas where smaller seasonal movements are observed, suggesting an unsaturated soil where water occurs in the deeper part of the active layer. Key Points: Multiannual InSAR observations of ground movement related to permafrost activity through the entire seasonal cycle over 60, 000 km 2 in Tibet Amplitude of warm season subsidence patterns associated with active layer thawing correlate with Cenozoic sedimentary basins Water/ice content in permafrost active layer controls amplitude and timing of maximum subsidence